2016
DOI: 10.1177/1757975916636792
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, social norms and perceived behavioral control factors influencing participation in a cooking skills program in rural Central Appalachia

Abstract: A focus group session, using the Theory of Planned Behavior to guide questions and discussion, was conducted at midpoint of a 12-month cooking skills program in a rural Appalachian food desert. The purpose of this qualitative study was to determine the attitudes, subjective norms and perceived behavioral control beliefs that influenced participation in these classes. Participants viewed the classes as opportunities for social interaction and to have new experiences. Subjective norms were influenced by family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Hence, we can conclude that the intervention implemented in the present study was not effective in increasing perceived behavioral control. This finding can be explained by the fact that perceived behavioral control is affected by barriers,[ 19 31 ] and on the other hand, there are many barriers in front of CRC cancer screening intention and behavior including traffic problems, lack of time, fatigue and boredom, feeling ashamed of doing these tests, and feelings of fear and anxiety until the test results are known. [ 11 ] In the present study, there was not enough time and facilities to influence all of these barriers, so change in the perceived behavioral control was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we can conclude that the intervention implemented in the present study was not effective in increasing perceived behavioral control. This finding can be explained by the fact that perceived behavioral control is affected by barriers,[ 19 31 ] and on the other hand, there are many barriers in front of CRC cancer screening intention and behavior including traffic problems, lack of time, fatigue and boredom, feeling ashamed of doing these tests, and feelings of fear and anxiety until the test results are known. [ 11 ] In the present study, there was not enough time and facilities to influence all of these barriers, so change in the perceived behavioral control was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…An individual’s attitude to something, his/her perceived desire of peer group of people (subjective norms) and perceived level of difficulty or barriers determine his/her intention to perform the behavior [ 47 ]. The theory of reasoned action (TRA), considers behavioral intention to perform or not to perform a specific action as the best predictor of reasoned action.…”
Section: The Theoretical Explanations and Hypothesis Developmentmentioning
confidence: 99%
“…Some participants in this study reported difficulty eating with friends/family and choosing low sodium options at restaurants as additional barriers. Overcoming these obstacles requires the presence of adequate resources, the ability to control barriers to behaviours and improved health literacy (Lambert et al ; Hardin‐Fanning & Ricks ; Lambert et al . ).…”
Section: Discussionmentioning
confidence: 99%